Pendampingan Pelaporan SPT PPH Orang Pribadi dan Sosialisasi PMK Nomor 168 Tahun 2023 - Riza Edwindra; Desak Rurik Pradnya Paramitha Nida; I Made Sastra Dwikiarta (Postgraduated Community Service Journal, 2024)
before the end of March. Tax return reporting is mandated in the Law on General Provisions and Tax Procedures (KUP) article 3, where every taxpayer is required to fill out the tax return correctly, clearly and completely, and for the annual income tax return, it must be submitted no later than 3 months after the tax year ends (March). Tax return reporting can be done online, using e-form or e-filling. However, there are still many people who still do not understand the reporting process using e-filling. The people in the Renon area are very homogeneous. The Renon area is considered very promising, until now it is still an "elite area" in the city of Denpasar. It is very strategically located, close to the center of the city government, even the province. There are many government and private offices, restaurants, restaurants, shops, and even the center of Beauty Clinics in Bali. The population of Renon in 2016 was 20,774 people, consisting of 10,331 men and 10,443 women. Very few residents in this area are unemployed, having an income means that many taxpayers are scattered in this area. The method used in this service is to provide direct assistance to the community. Includes assistance and consultation regarding the rights and obligations of taxpayers, matching NIK and NPWP and reporting Personal Tax using e-filling. The series of activities will be carried out continuously from February to March 2024. This activity was very welcomed by the community. However, the level of public awareness in fulfilling tax obligations is still quite lacking. This may happen due to the lack of public trust in the management of state finances due to the impact of corruption reporting by state apparatus. In addition to socialization, an important thing that must be fixed is the eradication of KKN to increase public trust.